2023
DOI: 10.2337/dc22-2189
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Continuous Glucose Monitoring Is Linked to Improved Glycemic Control and Fewer Clinical Events in Type 1 and Type 2 Diabetes in the Veterans Health Administration

Abstract: OBJECTIVE To determine the benefit of starting continuous glucose monitoring (CGM) in adult-onset type 1 diabetes (T1D) and type 2 diabetes (T2D) with regard to longer-term glucose control and serious clinical events. RESEARCH DESIGN AND METHODS A retrospective observational cohort study within the Veterans Affairs Health Care System was used to compare glucose control and hypoglycemia- or hyperglycemia-related admission to a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…The RELIEF study has also confirmed that the use of scanning CGM in people with T2D on basal insulin treatment is also associated with significantly reduced rates of hospital admission for DKA and severe hypoglycemia, for at least 2 years after initiation of scanning CGM [ 20 ]. Other studies have shown that using scanning CGM compared to SMBG is associated with a 25–40% reduction in all-cause hospital admissions for people with T1D [ 25 , 26 ] and a 11–15% reduction in all-cause admissions for people with T2D treated with insulin [ 25 , 27 ]. Given that the costs of hospitalization can be as high as €4835 for each person with diabetes and significant comorbid disease in Italy (Table 5 , Supplementary Table S1 ), such reductions in hospital admission can be substantial.…”
Section: Discussionmentioning
confidence: 99%
“…The RELIEF study has also confirmed that the use of scanning CGM in people with T2D on basal insulin treatment is also associated with significantly reduced rates of hospital admission for DKA and severe hypoglycemia, for at least 2 years after initiation of scanning CGM [ 20 ]. Other studies have shown that using scanning CGM compared to SMBG is associated with a 25–40% reduction in all-cause hospital admissions for people with T1D [ 25 , 26 ] and a 11–15% reduction in all-cause admissions for people with T2D treated with insulin [ 25 , 27 ]. Given that the costs of hospitalization can be as high as €4835 for each person with diabetes and significant comorbid disease in Italy (Table 5 , Supplementary Table S1 ), such reductions in hospital admission can be substantial.…”
Section: Discussionmentioning
confidence: 99%
“…This lower adherence among isCGM users compared to rtCGM users is notable because CGM use is associated with reductions in A1C and a lower risk of acute and long-term diabetes complications [ 3 , 4 , 16 19 ]. It is unknown whether people using insulin who stopped using CGM returned to self-monitoring of blood glucose (SMBG) regimens or administered insulin with little to no information about their glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical trials and real-world evidence studies of CGM have demonstrated improvement in glycaemic control, acute care use, and quality-of-life outcomes for adults with T2D. [79][80][81][82] Furthermore, in a recent study of intermittent short-term use of real-time CGM, this appears to be an effective method for glucose control in adults with T2D treated with oral agents, especially when combined with traditional self-monitoring of blood glucose. 83 CGM use in adults with T2D is now recommended within authoritative clinical guidelines.…”
Section: Crossing the Digital Divide In T2dmentioning
confidence: 99%